The Global Boundary Stratotype Section and Point (GSSP) of the Campanian Stage at Bottaccione (Gubbio, Italy) and its Auxiliary Sections:Seaford Head (UK), Bocieniec (Poland), Postalm (Austria), Smoky Hill, Kansas (U.S.A), Tepayac (Mexico) - Gale, Andy; Batenburg, Sietske; Coccioni, Rodolfo; Dubicka, Zofia; Erba, Elisabetta; Falzoni, Francesca; Haggart, Jim; Hasegawa, Takishi; Ifrim, Christina; Jarvis, Ian; Jenkyns, Hugh; Jurowska, Agata; et al. (Episodes, 2023)
Following the unanimous vote of the Executive Committee of International Union of Geological Sciences in October 2022, the Global boundary Stratotype Section and Point for the base of the Campanian Stage is confirmed as the magnetic polarity reversal from Chron 34n (top of the Long Cretaceous Normal Polarity–Chron) to Chron C33r at the 221.53 m level in the Bottaccione Gorge section at Gubbio, Umbria–Marche Basin, Italy. This event has been widely identified in oceanic settings and in widespread onshore outcrops. Sedimentation across the Santonian–Campanian boundary interval in the proposed GSSP appears to be continuous, supported by evidence from the carbon isotope record and complete micro– and nannofossil biostratigraphy. The succession comprises deep–water cherty limestones (mudstones and foraminiferal wackestones) which provide a detailed record of calcareous nannofossils and planktonic foraminifera and yields an excellent palaeomagnetic record. The high–resolution carbon isotope record, derived from bulk sediment, provides an important additional means of correlation to other regions.